Interdependence of noise and traffic flow - Bazaras, Jonas; Jablonskytė, Janina; Jotautienė, Eglė (Transport, 2008)
Traffic flows in cities, especially in city centres, are intensive and uneven, moreover, registered noise levels exceed allowable limits. Noise levels have been measured at K. Mindaugo ave. and Birštono street crossing in Kaunas and data of automated traffic flow registration equipment have been used. A constant reduction of noise level from the beginning till the end of the green light has been identified – “hot starts” generated noise dominates. To make estimates of noise and traffic flow interdependency, mathematical statistical models have been applied. Parameter distribution patterns have been analysed, prediction models have been composed. First published online: 27 Oct 2010